Evaluation of dimensional stability, weathering and decay resistance of modified pine wood byin-situpolymerization of styrene - Ermeydan, Mahmut Ali; Babacan, Mert; Dizman Tomak, Eylem (Taylor & Francis Inc, 2020)
In this study, polystyrene modified Scots pine (Pinus sylvestrisL.) wood was investigated upon artificial weathering, decay resistance, dimensional stability and water uptake properties. Polystyrene modification was carried out on pretreated wood by immersion of wood into styrene monomer and further polymerization. The resistance of modified wood against cycles of UV and water exposures was examined by artificial weathering test for 672 hours, and decay resistance was evaluated by attacks ofConiophora puteanaandTrametes versicoloron the samples. During the artificial weathering, color and surface roughness of the samples, and macroscopic changes were determined periodically. Changes in the surface chemistry and morphology of the weathered samples were investigated by ATR-FTIR and SEM, respectively. It was proven that polystyrene effectively protected pine samples from both fungi even after leaching procedure, but it was more effective in preventingC. puteanaattacks thanT. versicolorattacks. As a result of artificial weathering, the surface of all samples was darkened. However, changes in color and roughness as well as crack formations of the modified sample surfaces were found less than those of the untreated samples. Polystyrene also provided considerable improvement on dimensional stability, as well as water repellence of wood.
Keywords: Wood; polystyrene; dimensional stability; decay resistance; artificial weathering